Analyze of the Science Teacher's Profession Considered on Policy, Roles and Positions Based on The Teacher Law 2005 - Azmi, Dina Nabilatul; Mahardika, I. Ketut; Mutmainah, Nurrotul; Lestari, Puji; Sutarto, Sutarto (Peneliti.net, 2024)
This study aims to understand the importance of improving the quality of education by understanding the understanding, policies, roles and positions of the vocational profession. The understanding of the vocational profession includes important aspects related to the learning process, such as the application of knowledge, skills, and the application of educational values. The vocational profession refers to work related to education and teaching. Teachers themselves play a very important role in educating and teaching students. In addition to teaching and educating, teachers also need to know about the policies, roles and positions of the vocational profession. Teachers play an important role not only as informants, but also as study companions and personal guides. The position of vocational college in society aims to form the character and knowledge of successive generations. Therefore, by knowing the understanding, policies, roles and positions of teachers can devise strategic steps in the future to improve the quality of education.